2022
DOI: 10.7759/cureus.21257
|View full text |Cite
|
Sign up to set email alerts
|

Malaysian Public Interest in Common Medical Problems: A 10-Year Google Trends Analysis

Abstract: BackgroundAn analysis of internet search has been performed to evaluate the public interest in health problems. Google Trends (GT) serves as a free platform to analyse the search traffic for specific terms in the Google search engine. This observational study aims to investigate the trend of Malaysian population in using the Google search engine on common medical problems and explore the geographical influence on the language used. Material and methodFifteen pairs of keywords, in Malay and English language, we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(20 citation statements)
references
References 17 publications
0
20
0
Order By: Relevance
“…Google Trends is an objective data source being increasingly used in health care research [9]. These trends have proven to be especially useful in gauging general awareness regarding public health issues [10,11]. The search trends included in the present article give valuable insight into the minds of US citizens on the background of the Roe vs. Wade verdict.…”
Section: Discussionmentioning
confidence: 99%
“…Google Trends is an objective data source being increasingly used in health care research [9]. These trends have proven to be especially useful in gauging general awareness regarding public health issues [10,11]. The search trends included in the present article give valuable insight into the minds of US citizens on the background of the Roe vs. Wade verdict.…”
Section: Discussionmentioning
confidence: 99%
“…Considering the ongoing COVID-19 pandemic, this is the first study in Malaysia that investigates the behavior of public interest in COVID-19 vaccination using GT analysis. A 10-year GT analysis by Kow et al reveals that GT is a viable platform to track healthcare interest among the Malaysian population, despite a geographical variation in the language used [ 17 ]. Similar behavior has been noted by Izhar and Torabi and Lim et al whereby the Malaysian public has been using Google search extensively to enquire information related to COVID-19 during the pandemic [ 18 , 19 ].…”
Section: Discussionmentioning
confidence: 99%
“…First and foremost, this study uses Google Trends which only analyses the search behavior of people using the Google search engine. Nevertheless, as previous studies have indicated, Google is an overwhelming search engine of choice among Malaysians, hence the risk of bias will be kept to a minimum [ 17 ]. In addition, keywords used in GT analysis will affect SVI.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations